👤

Zapisz w postaci jednej potęgi. Skorzystaj z rozwiązania poprzedniego zadania.
[tex]( {27}^{5} \times { {9}^{12} )}^{3} = [/tex]


Odpowiedź :

Rozwiązanie:

[tex](27^5*9^{12})^{3}=((3^{3})^{5}*(3^{2})^{12})^{3}=(3^{15}*3^{24})^{3}=(3^{39})^{3}=3^{117}[/tex]

[tex]\left(27^5\cdot \:9^{12}\right)^3=\left(27^5\right)^3\cdot \left(9^{12}\right)^3=27^{15}\cdot \left(9^{12}\right)^3=27^{15}\cdot \:9^{36}=\left(3^3\right)^{15}\cdot \:9^{36}=3^{3\cdot \:15}\cdot \:9^{36}=3^{45}\cdot \:9^{36}=3^{45}\left(3^2\right)^{36}=3^{45}\cdot \:3^{2\cdot \:36}=3^{45}\cdot \:3^{72}=3^{45+72}=\boxed{3^{117}}[/tex]